Treatment of Complex Intracranial Aneurysms with a Telescoping Stent Technique - Chalouhi, Nohra; Campbell, Peter; Makke, Yamane; Yadla, Sanjay; Dumont, Aaron S.; Gonzalez, L. Fernando; Tjoumakaris, Stavropoula; Albani, Barbara; Rosenwasser, Robert H.; Jabbour, Pascal (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2012)
Background and Object Complex intracranial aneurysms present a treatment challenge for both open and endovascular modalities of treatment. This report seeks to illustrate a series of patients with aneurysms treated with telescoping stents as a method of flow diversion for small and fusiform intracranial aneurysms.Material and Methods A retrospective evaluation of six patients treated with a telescoping stent technique utilizing available stents (at that time before the pipeline era) for complex cerebral aneurysms between January 2009 and January 2010 was performed. Five patients had dissecting aneurysms and one patient had a small superior hypophyseal artery aneurysm. One of the patients was treated in the setting of a Hunt and Hess grade IV subarachnoid hemorrhage. Follow-up cerebral angiography was performed postprocedure at 6 months.Results At a mean follow-up period of 9 months, all the patients experienced complete or near-complete occlusion (>95%). No periprocedural complications were noted in this series. No episodes of hemorrhage or thromboembolic complications occurred.Conclusions Overlapping Neuroform and Enterprise stents may induce complete thrombosis of intracranial aneurysms and facilitate parent artery remodeling. The use of self-expanding stents is still an adequate treatment modality, especially if there is a need for vessel wall stabilization rather than flow diversion. The technique is also a sufficient alternative in small intracranial aneurysms not readily amenable to open surgical treatment or traditional endovascular coil embolization.
Keywords: sole stenting technique; aneurysm; endovascular; neuroform; enterprise; telescoping